2018
DOI: 10.2478/prolas-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Formation of Conjugated Dienes in Linseed Oil

Abstract: Oxidation of fats and oils reduces the nutritional value of food and causes various health problems. The addition of antioxidants prevents the oxidation of fats in the food. The antioxidant activity of antioxidants represents the ability to inhibit the process of oxidation. The antioxidant activity of herbal extracts has usually been assessed in a linoleic acid emulsion system. The aim of the present study was to evaluate inhibition of conjugated diene formation in Latvian linseed oil. Ethanol extract of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The works [8,[18][19][20][21][22][23] present data on various methods of oxidative stabilization of linseed oil using special storage films that absorb oxygen, as well as various types of antioxidants. Thus, the authors [22] showed the effectiveness of ascorbic acid esters.…”
Section: Discussion Of the Results Of Determining The Rational Concen...mentioning
confidence: 99%
See 1 more Smart Citation
“…The works [8,[18][19][20][21][22][23] present data on various methods of oxidative stabilization of linseed oil using special storage films that absorb oxygen, as well as various types of antioxidants. Thus, the authors [22] showed the effectiveness of ascorbic acid esters.…”
Section: Discussion Of the Results Of Determining The Rational Concen...mentioning
confidence: 99%
“…But darkening of the oil was detected when lycopene was added. According to [20], plant antioxidants are effective in inhibiting the oxidation of linseed oil at a temperature of 60 °C. Antioxidant activity was characterized by the percentage of formation of conjugated dienes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…H. sabdariffa is known for its anti-bacterial, anti-oxidant, diuretic, anti-cholesterol, anti-diabetic, anti-hypertensive, and anti-cancer activities. [ 9 10 ] The H. sabdariffa has gained significant attention in recent years due to its potential applications. The many studies have demonstrated the effectiveness of the methanolic extract of H. sabdariffa in inhibiting the growth and proliferation of pathogenic bacteria.…”
Section: R Esult and Discussionmentioning
confidence: 99%